2022
DOI: 10.1038/s41467-022-29250-3
|View full text |Cite
|
Sign up to set email alerts
|

Structures of pseudorabies virus capsids

Abstract: Pseudorabies virus (PRV) is a major etiological agent of swine infectious diseases and is responsible for significant economic losses in the swine industry. Recent data points to human viral encephalitis caused by PRV infection, suggesting that PRV may be able to overcome the species barrier to infect humans. To date, there is no available therapeutic for PRV infection. Here, we report the near-atomic structures of the PRV A-capsid and C-capsid, and illustrate the interaction that occurs between these subunits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 61 publications
0
13
0
Order By: Relevance
“…Based on these findings, we sought to match the DNA origami scaffold diameter to approximately that of the virus (in the range of 0.5–2× the diameter of the virus). PRV particles are approximately 150–200 nm in diameter. We chose a wireframe DNA origami design to achieve a stable 3D architecture at physiological Mg 2+ concentrations with diameters of ∼100 nm. For a given scaffold strand length, the wireframe design enables DNA origami architectures with large surface area-to-volume ratios.…”
Section: Resultsmentioning
confidence: 99%
“…Based on these findings, we sought to match the DNA origami scaffold diameter to approximately that of the virus (in the range of 0.5–2× the diameter of the virus). PRV particles are approximately 150–200 nm in diameter. We chose a wireframe DNA origami design to achieve a stable 3D architecture at physiological Mg 2+ concentrations with diameters of ∼100 nm. For a given scaffold strand length, the wireframe design enables DNA origami architectures with large surface area-to-volume ratios.…”
Section: Resultsmentioning
confidence: 99%
“…The clinical symptoms of sick pigs are very serious. The main pathological changes are encephalomyelitis, ganglionitis, hemorrhagic pneumonia, and necrotizing lymphadenitis, which can lead to death in severe cases ( 1 , 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Pseudorabies virus (PRV) is also known as porcine herpes virus type I, infectious bulbar paralysis virus, and so on. PRV is very common in pig infection, but there are few reports on PRV-infected people ( 1 , 2 ). We evaluated a case of encephalitis with unknown etiology, rapid onset, severe clinical manifestations such as fever, epilepsy, disturbance of consciousness and visual impairment, and detected pseudorabies virus by second-generation sequencing (NGS).…”
Section: Introductionmentioning
confidence: 99%
“…For viruses, resveratrol treatment relieved the inflammation response by inhibiting the TNF-α production and inhibited rotavirus infection by enhancing the IFN-γ content and CD4 + /CD8 + ratio, decreasing the diarrhea index [ 103 ]. Pseudorabies virus infection results in severe disruption of the pig production and massive economic loss [ 133 ]. Zhao et al [ 104 ] showed that resveratrol treatment for 7 d before and for 21 d after Pseudorabies virus infection could reduce the lesional scores of organs (brain, lung, kidney, liver, spleen and heart), increase the levels of TNF-α, IFN-α, IFN-γ, and IL-12 of the serum in weaned piglets, decreasing the inflammation, viral reproduction and lethality.…”
Section: Application Of Resveratrol In Swine Productionmentioning
confidence: 99%